The Role of the Head of the Neighborhood Association (RT) in the Implementation of the Population Information System - Sumiati, Sumiati; Mustika, Mustika; Irma Suryani, Ade (International Journal of Innovation Research in Education, Technology and Management, 2025)
This study examines the role of the RT (Neighborhood Association) head in managing the Population Information System in Mekar Sari Village, Kumpeh District, Muaro Jambi Regency. Mekar Sari Village consists of 17 RTs, each of which is responsible for handling population data such as birth, death, and migration reports. This study uses a descriptive qualitative method, with primary and secondary data collection through observation and interviews with the RT head and related parties. The research findings indicate that although the RT head plays an important role in compiling, updating, and reporting population data, its implementation is still ineffective. The main obstacles include time constraints, low community participation, and late reporting to the village government. These findings highlight the need for increased support and system improvements to ensure more effective population data management, which in turn can better support overall village administration.